Understanding sociology - Calhoun, Craig J., 1952-; Light, Donald, 1942-; Keller, Suzanne (New York : McGraw - Hill, 1995)
[The authors] have tried to make this a book students will want to r ead as well as a book from which they will learn about the best of cont emporary and classical sociology.... The concepts of functional integra tion, power, social action, social structure, and culture are presented as major tools of sociological work.--Pref.
Study of sociology: Sociological perspective; Methods of sociologica l research; Culture; Interaction and social structure -- Individual and society: Socialization; Life course, from childhood to old age; Devian ce and crime; Groups and organizations -- Inequality and power: Class a nd stratification; Race and ethnicity; Sex and gender -- Social institu tions: Family; Education; Religion; Health and health care; Economics a nd work; Politics, the State, and war -- Global challenges: Third world ; Population and environment; Communities and urbanization; Social move ments and collective action; Social change -- Glossary.
Includes bibliographical references (p. [593]-618) and indexes.
Keywords: Sociology